Islamic Religious Education Teachers' Strategies in Dealing with the Brain Rot Phenomenon in Students - Ryan Prawoko; Luqi Darmawan; Muhammad Syuhada Subir (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
The phenomenon of brainrot as a form of degradation of cognitive, affective, and psychomotor functions due to excessive consumption of instant and superficial digital content has become a serious challenge in the world of education. This study aims to explore the strategies of Islamic Religious Education (PAI) teachers in dealing with the phenomenon of brainrot in students of SMK Ma'arif Sudimoro. This study uses a qualitative approach using a case study method. Data collection techniques were carried out through interviews, classroom observations, and documentation, which were analyzed using Miles, Huberman, and Saldana analysis techniques. The results of the study show that Islamic Religious Education teachers apply three main strategies, namely: (1) contextual learning that relates PAI material to digital phenomena that are close to students' daily lives; (2) group discussion strategies that encourage active participation and critical thinking of students; and (3) a reflective-spiritual approach that fosters self-awareness and religious values through contemplation and spiritual experience. Although this strategy is effective in increasing student engagement and instilling religious values, its implementation is faced with a number of challenges, including low student focus, resistance to reflective values, and reliance on instant culture. Teachers respond to these challenges by innovating learning media, sharing roles in discussions, and strengthening digital-based reflection methods. This study concludes that adaptive, relevant, and spiritual value-based learning strategies can be a solution to minimize the impact of brainrot, while strengthening students' religious character in the digital era and is expected to be a contextual and transformative reference.